(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The demand for electricity in the world is increasing and there is requirement of harnessing different kinds of renewable energies. Worldwide efforts have turned towards most reliable renewable energy source; wind power. In wind energy conversion systems, large research and development has observed in the area of The Horizontal Axis Wind Turbine (HAWT) than Vertical Axis Wind Turbine (VAWT). This paper describes the development and performance analysis of Porthole Type Vertical Axis Wind Turbine. The model of Porthole Type Vertical Axis Wind Turbine (PTVAWT) is fabricated and tested to predict the performance in terms of shaft speed, torque and power. The wind turbine model has radius of 500 mm and height of 850 mm. The analysis is carried out by varying control parameters such as wind speed and porthole angle. The effect of control parameters on the response parameters i.e. shaft speed, torque and power has been analyzed by conducting the various experiments. The response parameters are increases with increase in the wind speed and maximum values are obtained at wind speed of 21 m/s. The response parameters are increases up to 40Â° porthole angle and then decreases by increasing the porthole angle more than 40°.